Definition:Ackermann Function/Examples

From ProofWiki
Jump to navigation Jump to search

Examples of Ackermann Function

The Ackermann function $A: \Z_{\ge 0} \times \Z_{\ge 0} \to \Z_{> 0}$ is defined as:

$A \left({m, n}\right) = \begin{cases} 2 n & : m = 1 \\ m & : m > 1, n = 1 \\ A \left({m - 1, A \left({m, n - 1}\right)}\right) & : \text{otherwise} \end{cases}$


$\begin{array}{c|c|c|c} A \left({m, n}\right) & m = 1 & m = 2 & m = 3 & m = 4 & \cdots & m = k \\ \hline n = 1 & 2 & 2 & 3 & 4 & & k \\ n = 2 & 4 & \map A {1, \map A {2, 1} } & \map A {2, \map A {3, 1} } & \map A {3, \map A {4, 1} } & & \map A {k - 1, \map A {k, 1} } \\ n = 3 & 6 & \map A {1, \map A {2, 2} } & A \map A {2, \map A {3, 2} } & \map A {3, \map A {4, 2} } & & \map A {k - 1, \map A {k, 2} } \\ n = 4 & 8 & \map A {1, \map A {2, 3} } & \map A {2, A \map A {3, 3} } & \map A {3, \map A {4, 3} } & & \map A {k - 1, \map A {k, 3} } \\ n = 5 & 10 & \map A {1, \map A {2, 4} } & \map A {2, \map A {3, 4} }\ & \map A {3, \map A {4, 4} } & & \map A {k - 1, \map A {k, 4} } \\ \vdots & & & & & & \\ n = j & 2 j & \map A {1, \map A {2, j - 1} } & \map A {2, \map A {3, j - 1} } & \map A {3, \map A {4, j - 1} } & & \map A {k - 1, \map A {k, j - 1} } \\ \end{array}$


which leads to:

$\begin{array}{c|c|c|c} A \left({m, n}\right) & m = 1 & m = 2 & m = 3 & m = 4 & \cdots & m = k \\ \hline n = 1 & 2 & 2 & 3 & 4 & & k \\ n = 2 & 4 & 4 & 8 & \map A {3, 4} & & A \map A {k - 1, k} \\ n = 3 & 6 & 8 & 2^8 & \map A {3, \map A {4, 2} } & & \map A {k - 1, \map A {k, 2} } \\ n = 4 & 8 & 16 & 2^{2^8} & \map A {3, \map A {4, 3} } & & \map A {k - 1, \map A {k, 3} } \\ n = 5 & 10 & 32 & \map A {2, \map A {3, 4} } & \map A {3, \map A {4, 4} } & & \map A {k - 1, \map A {k, 4} } \\ \vdots & & & & \\ n = j & 2 j & 2^j & \map A {2, \map A {3, j - 1} } & \map A {3, \map A {4, j - 1} } & & \map A {k - 1, \map A {k, j - 1} } \\ \end{array}$




Sources